Pendampingan Manajemen Dasar-dasar Pariwisata untuk Keberlanjutan dan Pengembangan Produk Destinasi Wisata - Aletta Dewi Maria Th; Dyah Palupiningtyas; Tuwuh Adhistyo (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Tourism has become one of the vital sectors in the economic development of a region. To ensure the sustainability and development of tourism destination products, effective assistance in basic tourism management is necessary. This study aims to describe the mentoring process and analyze its impact on the sustainability and development of tourism destination products. This community service focuses on assisting the management of tourism fundamentals, emphasizing managerial capacity building, strengthening community involvement, and developing sustainable tourism destination products. This assistance has successfully increased understanding and skills in basic tourism management among stakeholders. The involvement of local communities in tourism-related decision-making has also increased, ensuring active participation and shared responsibility in managing tourism destinations. Furthermore, this mentoring encourages innovation in the development of sustainable and competitive tourism products. Thus, assistance in basic tourism management not only has a positive impact on sustainability but also serves as a catalyst for the development of tourism destination products that provide significant added value to the local economy and community welfare. Practical implications and recommendations for policies are also discussed to strengthen efforts in developing sustainable tourism